Brazil's National Program for Improving Primary Care Access and Quality (PMAQ) Fulfilling the Potential of the World's Largest Payment for Performance System in Primary Care - Macinko,J; Harris,MJ; Rocha,MG (Journal of Ambulatory Care Management, 2017)
Despite some remarkable achievements, there are several challenges facing Brazil's Family Health Strategy (FHS), including expanding access to primary care and improving its quality. These concerns motivated the development of the National Program for Improving Primary Care Access and Quality (PMAQ). Although voluntary, the program now includes nearly 39 000 FHS teams in the country and has led to a near doubling of the federal investment in primary care in its first 2 rounds. In this article, we introduce the PMAQ and advance several recommendations to ensure that it continues to improve primary care access and quality in Brazil.